Value is in the Eye of the Beholder: The Relative Valuation Roles of Earnings and Book Value in Merger Pricing - Rabier, MaryJane R. (The Accounting Review, 2018)
ABSTRACT Gupta and Gerchak (2002) argue that different acquirers can arrive at different equity valuations for the same target depending on their strategic intent. A reason for acquirers' equity valuations to vary, holding target fundamentals constant, may be that individual acquirers place different weights on underlying fundamentals. I examine this possibility using Burgstahler and Dichev's (1997) theoretical framework. They argue that the relative importance of earnings and book value depends on expected adaptation, which is the likelihood that the existing earnings generating process will be altered. Using restructuring costs to proxy for expected adaptation at the individual acquirer level, I find that the association between the target's earnings (book value) and acquirers' bid prices is decreasing (increasing) in expected adaptation, consistent with theoretical predictions. These findings are less pronounced during merger waves and intense bid competition for the target.